Concurrent sigmoid volvulus and caecal adenocarcinoma in a paraplegic patient with neurogenic bowel: a case report - Nakul Ganju; Alvin Billey; Juan Carlos Santiago-Gonzalez; Angesom Kibreab (Journal of Surgical Case Reports, 2026)
Abstract A 76-year-old man with paraplegia and neurogenic bowel dysfunction presented with progressive abdominal distension and altered bowel habits. Contrast-enhanced computed tomography demonstrated sigmoid volvulus and an incidental 5 × 4 cm ileocaecal mass. After endoscopic detorsion, multidisciplinary review recommended definitive resection during the same admission. He underwent right hemicolectomy with ileocolic anastomosis and sigmoidectomy with colorectal anastomosis. Histopathology confirmed moderately differentiated caecal adenocarcinoma (pT3N1a, R0). The postoperative course was complicated by aspiration pneumonitis and femoral deep venous thrombosis, both managed successfully. This case illustrates that neurogenic bowel dysfunction may mask coexistent colorectal malignancy, and that unexplained microcytic anaemia in a patient presenting with volvulus warrants comprehensive colonic evaluation. Perioperative management in this population requires multidisciplinary input to address the elevated risks of cardiopulmonary and thromboembolic complications.